Determinants of HIV voluntary counseling and testing: a multilevel modelling of the Ethiopian Demographic and Health Survey - Adugnaw Zeleke Alem; Achamyeleh Birhanu Teshale; Alemneh Mekuriaw Liyew; Getayeneh Antehunegn Tesema; Ayenew Kassie Tesema; Yigizie Yeshaw (BMC Women's Health, 2022)
Abstract Background Human immunodeficiency virus (HIV) counseling and testing services are vital to reduce the spread of HIV infection, and to create an opportunity for early treatment and reduction of HIV/AIDS-related mortality. However, only 12 sub-Saharan African (SSA) countries reached the first 90% target (90% of people living with HIV to know their status). Hence, this study aimed to investigate the determinants of HIV counseling and testing among reproductive-age women in Ethiopia. Methods Ethiopian Demographic and Health Survey (EDHS 2016) data was used to identify the determinants of HIV counseling and testing among reproductive-age women in Ethiopia. A weighted sample of 14,599 reproductive age women was included in the study. A multilevel binary logistic regression model was fitted to identify the determinants of HIV counseling and testing. The odds’ ratio with a 95% Confidence Interval (CI) and the corresponding P-value ≤ 0.05 was employed to declare the statistically significant variables. Results In this study, both individual and community-level variables were significantly associated with Voluntary Counseling and Testing (VCT) uptake among women. Women aged 25–34 years (Adjusted Odds Ratio (AOR) 2.29, 95% CI 2.05, 2.56), aged ≥ 35 years (AOR 1.55, 95% CI 1.38, 1.75), attending primary education (AOR 1.68, 95% CI 1.51, 1.88), secondary education (AOR 3.07, 95% CI 2.64, 3.58), and higher education (AOR 5.15, 95% CI 4.17, 6.36), women with medium household wealth (AOR 1.56, 95% CI 1.32, 1.84), richer (AOR 1.88, 95% CI 1.58, 2.24), and richest wealth index (AOR 2.37, 95% CI 1.91, 2.94), having comprehensive knowledge (AOR 1.21, 95% CI 1.06, 1.37), ever married (AOR 3.87, 95% CI 3.46, 4.32), having sexual risky behavior (AOR 2.09, 95% CI 1.69, 2.49), women from communities with high HIV knowledge (AOR 2.03, 95% CI 1.68, 2.45), women from communities with high literacy level (AOR 1.16, 95% CI 1.05, 1.51) and women from communities with high wealth quintile (AOR 1.20, 95% CI 1.03,1.57) had higher odds of VCT uptake. However, those women having stigma (AOR 0.81, 95% CI 0.74, 0.92) had reduced odds of VCT uptake. Conclusion This study revealed that not only individual level factors but also community level factors determine the status of HIV voluntary counseling and testing. Hence, strengthening both individual and community based interventions are crucial to increase the women HIV counseling and testing practice in the country.